Agency and the making of transient urban spaces: examples of migrants in the city in the Pearl River Delta, China, and Dhaka, Bangladesh - Bork-Hüffer, Tabea; Etzold, Benjamin; Gransow, Bettina; Tomba, Luigi; Sterly, Harald; Suda, Kimiko; Kraas, Frauke; Flock, Ryanne (Population, space and place, 2016)
Internal migration within Asian countries and international migration to, within, and out of Asia have been on the rise throughout the past decades. As types and pathways of migration, migrants' sociocultural and socioeconomic backgrounds, and their transnational and translocal trajectories become increasingly diverse, a majority of them move to cities. Diverging power geometries and relations are constantly negotiated and (re)produced in the socio-spatial dialectic of the city. Through their individual and collective agency, assets, and knowledge, mobile subjects have become important agents in the (re)production of spaces in cities, whereas the socio-political and physical conditions of spaces frame their livelihoods, opportunities, and agency. Research on migrants' agency has intensified recently, but the specific modes through which agency operates in the socio-spatial dialectic still need to be conceptualised. We develop a framework that outlines different modes through which agents and space interact. The framework is exemplified through papers on case studies from Dhaka and the Pearl River Delta (PRD) that are part of this special issue. Dhaka and the PRD have been characterised by accelerated growth throughout the past decades, particularly due to the influx of rural-to-urban migrants, but they also receive an increasing number of international migrants. We conclude that through their diverse, multi-sited, and translocal relations and activities stretching beyond the receiving cities in a context of constant transformation, migrants' practices contribute to the emergence of a specific type of urban spaces that we delineate as transient urban spaces. Copyright © 2014 John Wiley & Sons, Ltd.
Gesehen am 22.04.2024
Online veröffentlicht: 28. Oktober 2014